Potensi Kaempferol dan Kalkon Tergeranilasi Sebagai Kandidat Terapi Penyakit Jantung Koroner (PJK) Melalui Pendekatan Molecular Docking - Saeful Amin; Tevani Almanda Ramdani; Maitsa Gita Salsabila; Teguh Nizar Zulmi (Pusat riset dan Inovasi Nasional, 2025)
Coronary heart disease (CHD) is one of the leading causes of death worldwide due to impaired blood and oxygen supply to the heart muscle. This study aims to explore the potential of two natural compounds—kaempferol from Moringa oleifera and geranylated chalcone (GTDC) from Artocarpus altilis—as therapeutic candidates for CHD through a molecular docking approach. Medicinal chemistry analysis revealed that kaempferol exhibits significant affinity for the NF-κB protein, forming key hydrogen bonds with residues involved in the inflammatory process of atherosclerosis. Meanwhile, GTDC demonstrates strong binding to the P2Y12 receptor, which plays a crucial role in platelet aggregation, with a docking score lower than that of the natural ligand ADP. Structurally, hydroxyl group positioning and the lipophilic geranyl chain enhance both bioactivity and pharmacokinetic properties. In conclusion, a medicinal chemistry approach involving in silico docking, structure–activity relationship (SAR) analysis, and ligand optimization strategies confirms the potential of kaempferol and GTDC as promising multifunctional therapeutic agents for CHD. Further validation through in vivo studies and clinical testing is required.